TROLLING FOR ENGAGEMENT: AUSTRALIAN LEGACY NEWS OUTLETS SEEKING AUDIENCE INTERACTION METRICS ON FACEBOOK THROUGH DELIBERATELY DIVISIVE CONTENT - Hurcombe, Edward (AoIR Selected Papers of Internet Research, 2019)
This paper empirically investigates how two prominent Australian legacy news outlets – ABC News and News.com.au – operate according to what I term a social media logic of “engagement”, a concept which builds upon van Dijck & Poell’s notion of a social media logic of “popularity”. By a logic of engagement, I mean the necessity to maximize social media attention and interaction metrics. Rather than just valuing “popularity”, platforms instead place value on content that maximizes a multitude of feelings, sentiments, and reactions. Without sufficient engagement, outlets dependent on platforms such as Facebook are threatened by invisibility in the newsfeed. I specifically focus on the operations of ABC News and News.com.au on Facebook from 21 March 2018 – 10 April 2018. Within this period, I collected all the posts from each page, which amounted to 44 posts in total. From these posts, I strategically selected six posts of varying levels of engagement for closer qualitative analysis, with an emphasis on language and imagery. My findings in this paper suggest that the drive for monetizable and algorithmically-valued audience metrics on Facebook can encourage divisive and provocative news content that arouses strong negative feelings and promotes conflict. Trolls are those that deceive other users of their intentions, and seek to sow discord for their own purposes. Thus, it is beneficial to think about a potentially emerging practice of news “trolling”, as it appears that news outlets are adopting faux-naïve, and deliberately incendiary, practices when pursuing engagement.